2023
DOI: 10.1186/s40168-023-01637-4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing gut microbiome-driven adipose tissue inflammation alleviates metabolic syndrome

N. K. Newman,
Y. Zhang,
J. Padiadpu
et al.

Abstract: Background The gut microbiota contributes to macrophage-mediated inflammation in adipose tissue with consumption of an obesogenic diet, thus driving the development of metabolic syndrome. There is a need to identify and develop interventions that abrogate this condition. The hops-derived prenylated flavonoid xanthohumol (XN) and its semi-synthetic derivative tetrahydroxanthohumol (TXN) attenuate high-fat diet-induced obesity, hepatosteatosis, and metabolic syndrome in C57Bl/6J mice. This coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, these were in very low abundance or absent from metagenomic or metatranscriptomic reads, aligning with findings from Dill-McFarland et al 13 Several abundant bacterial taxa identified, such as Clostridium, Corynebacterium, Oscillibacter, Pseudoflavonifractor, and Ruminococcus, are well-known residents of herbivore guts. These bacteria play crucial roles in fermenting and breaking down plant polysaccharides and detoxifying plant alkaloids and other secondary metabolites 17,42,50,[52][53][54][55] . For instance, Lachnospiraceae (Eubacteriales), one of the most abundant families found in the present study, is a group of obligately anaerobic bacteria that are among the most abundant taxa in the rumen 50 and in wild sloths 13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these were in very low abundance or absent from metagenomic or metatranscriptomic reads, aligning with findings from Dill-McFarland et al 13 Several abundant bacterial taxa identified, such as Clostridium, Corynebacterium, Oscillibacter, Pseudoflavonifractor, and Ruminococcus, are well-known residents of herbivore guts. These bacteria play crucial roles in fermenting and breaking down plant polysaccharides and detoxifying plant alkaloids and other secondary metabolites 17,42,50,[52][53][54][55] . For instance, Lachnospiraceae (Eubacteriales), one of the most abundant families found in the present study, is a group of obligately anaerobic bacteria that are among the most abundant taxa in the rumen 50 and in wild sloths 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly XH is also able to attenuate lipogenesis in cultured hepatocytes and protect against NAFLD in mice and rats by suppressing the hepatic SREBP1 and diacylglycerol acyltransferase (DAG), activation of farnesoid X receptor (FXR), antagonizing PPARγ, and stimulating the Nrf2/RAGE/NF-κB axis [48][49][50][51]. This data indicates that XH may act by various mechanisms under a common umbrella.…”
Section: Introductionmentioning
confidence: 94%
“…The microbiome also exerts influence over host metabolic inflammation, particularly in conditions such as obesity and metabolic syndrome [150,151]. Dysbiosis observed in these conditions can lead to changes in the production of inflammatory mediators and adipokines, ultimately contributing to a pro-inflammatory state.…”
Section: Microbiome-induced Changes In Host Barrier Permeabilitymentioning
confidence: 99%